Effect of CMMI-Based Software Process Maturity on Software Schedule Estimation - A. Alyahya, Maged; Ahmad, Rodina; Lee, Sai Peck (Malaysian Journal of Computer Science, 2009)
The Software Capability Maturity Model (SW-CMM) has become a popular model for enhancing software development processes with the goal of developing high-quality software within budget and schedule. The software cost estimation model, COnstructive COst MOdel (COCOMO), in its last update (COCOMO II) has a set of seventeen cost drivers and a set of five scale factors. Process Maturity (PMAT) is one of the five scale factors and its ratings are based on SW-CMM. This paper investigates the impact of process maturity on software development Schedule (cycle time) by deriving a new set of COCOMO II’s PMAT rating values based on the most recent version of CMM, i.e. Capability Maturity Model Integration (CMMI). The precise data for the analysis were collected from the record of 40 historical projects which spanned the range of CMMI Levels, from Level 1 (Lower half and Upper half) to Level 4, where eight data points were collected from each level. The Ideal Scale Factor (ISF) method is applied in order to withhold the effect of the COCOMO II’s PMAT scale factor. All prediction accuracies evaluations were measured using PRED (.20). The study shows that the proposed model (with the new PMAT rating values) produced better schedule estimates as compared to the generic COCOMO II model’s schedule estimates.